Cryopreservation of sperm in common carp Cyprinus carpio: sperm motility and hatching success of embryos - Linhart, O; Rodina, M; Cosson, J (Cryobiology, 2000)
In this study, fish sperm cryopreservation methods were elaborated upon for ex situ conservation of nine strains of Bohemian common carp. Common carp sperm were diluted in Kurokura medium and chilled to 4 degrees C and dimethyl sulfoxide was added. Cryotubes of sperm with media were then cooled from +4 to -9 degrees C at a rate of 4 degrees C min(-1) and then from -9 to -80 degrees C at a rate of 11 degrees C min(-1), held for 6 min at -80 degrees C, and finally transferred into liquid N(2). The spermatozoa were thawed in a water bath at 35 degrees C for 110 s and checked for fertilization yield, hatching yield of embryos, and larval malformations. Fresh and frozen/thawed sperm were evaluated for the percentage and for the velocity of motile sperm from video frames using image analysis. The percentage and velocity of sperm motility at 15 s after activation of frozen/thawed sperm was significantly lower than that of fresh sperm (nine males). ANOVA showed a significant influence of fresh vs frozen/thawed sperm on fertilization rate (P < 0.0001), but differences in hatching rate and in larval malformation (0-6.8%) were not significant, and different males had a significant influence on fertilization and hatching rate (P < 0.003 and P < 0.007, respectively). Multiple range analysis (LSD) showed significant differences between fresh and frozen/thawed sperm regarding fertilization rate (68 +/- 11 and 56 +/- 10%, respectively) and insignificant differences between fresh and frozen/thawed sperm on the hatching rate (50 +/- 18 and 52 +/- 9%, respectively). The percentage and velocity of fresh sperm motility were correlated, respectively, with the fertilization yield of frozen/thawed sperm at the levels r = 0.51 and r = 0.54.
Keywords: embryo nesavčí; Sperm Motility; kryoprezervace; Carps; motilita spermií; Animals; fertilizace; Cryopreservation; Male; Embryo, Nonmammalian; Fertilization; mužské pohlaví; spermie; Spermatozoa; zvířata; kapři